2005
DOI: 10.1007/s10549-005-1721-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of apoptosis, proliferation, HER-2, and topoisomerase IIα for anthracycline chemotherapy in locally advanced breast cancer

Abstract: In human primary breast cancer, anthracycline treatment causes an early increase in apoptosis and a decrease in proliferation. In this pilot study, higher apoptosis and topo IIalphaa levels in primary tumors were associated with greater responsiveness to anthracyclines, and topo IIalpha levels declined in responsive tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…Anthracycline derivatives, such as the doxorubicin used in this trial, have been found to induce both an early increase in apoptotic activity and a decrease in proliferation (35). We expect that cellular assays will correlate with DOS functional measurements of biochemical changes within 1 week posttherapy.…”
Section: Discussionmentioning
confidence: 89%
“…Anthracycline derivatives, such as the doxorubicin used in this trial, have been found to induce both an early increase in apoptotic activity and a decrease in proliferation (35). We expect that cellular assays will correlate with DOS functional measurements of biochemical changes within 1 week posttherapy.…”
Section: Discussionmentioning
confidence: 89%
“…Analyzing data from the literature on TOP2A status and its role as a predictive factor in invasive breast carcinoma is a confusing experience [18][19][20][21][22][23]. Outcomes of results both at the level of evaluation of TOP2A as well as at the level of interpretation are extremely different [24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…However, de novo and acquired resistance to therapy is observed in a significant subset of patients, leading to subsequent disease progression [149]. In contrast to predictive factors for targeted therapy, predictive markers for chemosensitivity are less well-defined [150,151]. Chemotherapy agents including CMF, taxanes and anthracycline-based chemotherapy affect cell division or DNA synthesis and function in some way.…”
Section: Proliferation Markersmentioning
confidence: 99%
“…Other markers that have been used as a predictor of outcome and response to therapy include Topoisomerase II alpha expression and (TOP2A) gene amplification (molecular target for anthracyclines) [98,150,163], Bcl2 and p53 expression [164,165]. TOP2A aberrations (amplification, deletion) are found in up to approximately 30-90% of HER2-amplified BC, and amplifications are more common than deletions.…”
Section: Additional Markersmentioning
confidence: 99%